The Effect of Entrepreneurship Training and Business Assistance on Strengthening the Role of MSME Players Assisted by PLUT-KUMKM in South Sulawesi Province - Nirwana Nirwana; Muhammad Rakib; M. Ihsan Said Ahmad; Syamsu Rijal; Muhammad Hasan (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2023)
This research was conducted to determine the effect of entrepreneurship training and business assistance on strengthening the role of MSME actors assisted by PLUT KUMKM Prov. South Sulawesi Makassar City. By using quantitative methods and sample collection, namely probability sampling. With partial and simultaneous tests. The results of this study are that there is a significant influence between entrepreneurship training and business assistance on strengthening the role of MSME actors assisted by PLUT-KUMKM Prov.South Sulawesi Makassar City. Partially, entrepreneurship training (X1) has an effect on strengthening the role of MSME actors and business assistance has an effect but not significant on strengthening the role of MSME actors. The percentage of the influence of entrepreneurship training and business assistance assisted by PLUT KUMKM South Sulawesi Province is 33.3%.